Comparison of the performance of four screening tools for sarcopenia in patients with chronic liver disease - Ting Yu; Shanshan Liu; Jing Zhao; Yan Jiang; Rong Deng (Elsevier, 2024)
Objectives: Early identification of sarcopenia in patients with chronic liver disease is crucial for patient management and prevention of severe complications. We aimed to assess the effectiveness of Ishii score, Strength, Assistance with Walking, Rise from a Chair, Climb Stairs and Falls (SARC-F), SARC-F and Calf Circumference (SARC-CalF), and Mini Sarcopenia Risk Assessment-7 (MSRA-7) to screen sarcopenia in patients with chronic liver disease. Methods: This prospective study included patients with chronic liver disease in the infectious department of a tertiary hospital in Sichuan, China. Ishii score, SARC-F, SARC-CalF, and MSRA-7 were used to screen for sarcopenia risk. Sarcopenia was diagnosed according to the Asian Myometriosis Working Group (AWGS) 2019, which was used as the gold standard to compare the performance of the four screening tools. We completed clinical registration on the Chinese Clinical Trial Registration website (ChiCTR2100043910). Results: A total of 366 patients with chronic liver disease (22.4% women, mean age 48.96 ± 11.88 years) were evaluated. Based on the AWGS 2019 standard, the prevalence of sarcopenia in patients with chronic liver disease was 17.5%. Among all participants, receiver operating characteristic (ROC) produced an area under the curve (AUC) of 0.82 for Ishii score (sensitivity 85.94%, specificity 78.15%), 0.53 for SARC-F (sensitivity 6.25%, specificity 99.34%), 0.64 for SARC-CalF (sensitivity 45.31%, specificity 83.11%), and 0.55 for MSRA-7 (sensitivity 87.50%, specificity 22.85%). Based on AUC, decision curve analysis, and calibration curves, we concluded that Ishii score was the most accurate screening tool and was superior to the other tools. Conclusions: Ishii score is more suitable for screening sarcopenia in patients with chronic liver disease than the SARC-F, SARC-CalF, and MSRA-7, based on the AWGS 2019 criteria. Nursing professionals can use Ishii score as a clinical tool to screen for sarcopenia in patients with chronic liver disease, providing an indication cue for the final diagnosis of sarcopenia, improving diagnostic efficiency, and enabling early identification and prevention of complications resulting from sarcopenia.